Better Regulation – An Ongoing Journey. (September 2015) - Chase, Peter; Schlosser, Adam
Abstract : The Commission's new Better Regulation package represents a step forward in the European Union's decade–long journey to bringing coherence and rationality to its legislative and regulatory process. But as the Communication on the package itself suggests, the journey is far from over. The Communication consistently emphasizes the key aspects of good regulation: quality over quantity; taking time to get proposals right; evidence–based decision making; open and continuous consultation to gather evidence from all stakeholders; rigorous impact assessments and cost–benefit analysis; applying these tools to regulatory measures as well as legislation; and implementing a robust ex–post evaluation program. It is important as well that the Secretariat General published unified and detailed guidance for Commission officials on how each step of the regulatory process should work, with a "tool–box" to elaborate further on these steps. All of this is good. Yet in some areas, the Commission misses opportunities to go farther down the good governance road, and in others the guidance needs to be made much more explicit.